2011
DOI: 10.1074/jbc.m111.252791
|View full text |Cite
|
Sign up to set email alerts
|

Altered Toll-like Receptor 2-mediated Endotoxin Tolerance Is Related to Diminished Interferon β Production

Abstract: Induction of endotoxin tolerance leads to a reduced inflammatory response after repeated challenge by LPS and is important for resolution of inflammation and prevention of tissue damage. Enterobacterial LPS is recognized by the TLR4 signaling complex, whereas LPS of some non-enterobacterial organisms is capable of signaling independently of TLR4 utilizing TLR2-mediated signal transduction instead. In this study we report that Porphyromonas gingivalis LPS, a TLR2 agonist, fails to induce a fully endotoxin toler… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 58 publications
0
19
0
Order By: Relevance
“…It was recently reported that TLR4 is superior to TLR2 in regard to IL-10 production because signaling via TRIF prevented degradation of IL-10 mRNA in macrophages (55). Furthermore, TRIF-dependent release of IFN-␤ has been implicated in endotoxin tolerance (56). However, the level of IFN-␤ induction by P. gingivalis is low and was previously suggested to depend on the presence of TLR7 (57).…”
Section: Discussionmentioning
confidence: 77%
“…It was recently reported that TLR4 is superior to TLR2 in regard to IL-10 production because signaling via TRIF prevented degradation of IL-10 mRNA in macrophages (55). Furthermore, TRIF-dependent release of IFN-␤ has been implicated in endotoxin tolerance (56). However, the level of IFN-␤ induction by P. gingivalis is low and was previously suggested to depend on the presence of TLR7 (57).…”
Section: Discussionmentioning
confidence: 77%
“…Zaric et al . showed that induction of tolerance could be achieved in gingival fibroblasts if IFN‐β was provided . Such a reduction in inflammatory response may provide a break in the inflammatory cycle and facilitate the induction of resolution.…”
Section: The Clinical Significance Of Stromal Memorymentioning
confidence: 99%
“…A possible example is periodontitis, in which microbiota and host immune responses conspire to produce the most common chronic inflammatory disease in the world [81]. Zaric et al showed that induction of tolerance could be achieved in gingival fibroblasts if IFN-b was provided [33]. Such a reduction in inflammatory response may provide a break in the inflammatory cycle and facilitate the induction of resolution.…”
Section: The Clinical Significance Of Stromal Memorymentioning
confidence: 99%
“…ET is an important and evolutionarily conserved mechanism protecting host animals from the tissue damage caused by excessive inflammation after exposure to an endotoxin (e.g., LPS) . Nonetheless, ET also serves as a key mechanism for sustained immunosuppression that is associated with the mortality of patients with sepsis in late phases .…”
Section: Discussionmentioning
confidence: 99%